Thermal Analysis on Radial Flux Permanent Magnet Generator (PMG) using Finite Element Method - Irasari, Pudji; Syaeful A, Hilman Syaeful A; Kasim, Muhammad (IPTEK The Journal for Technology and Science, 2011)
The main source of heat in the permanent magnet generator (PMG) is the total losses which f come from winding losses, core losses and rotational losses. Total heat arising from such these losses must be properly distributed and maintained so as not to exceed the maximum allowable temperature to prevent damage to insulation on the winding and demagnetization on the permanent magnet machines. In this research, we consider thermal analysis which is occurred on the radial flux PMG by using finite element method to determine the extent to which the heat generated can be properly distributed. The simulation results show that there are no points of heat concentration or hot spot. The simulation maximum temperatures of the permanent magnet and the winding are 39.1oC and 72.5oC respectively while the experimental maximum temperature of the winding is 62oC.